Head-mounted display-based application for cognitive training - Varela Aldas, José; Palacios-Navarro G.; Amariglio R.; García-Magariño I. (My University, 2020)
Virtual Reality (VR) has had significant advances in rehabilitation, due to the gamification of cognitive activities that facilitate treatment. On the other hand, Immersive Virtual Reality (IVR) produces outstanding results due to the interactive features with the user. This work introduces a VR application for memory rehabilitation by walking through a maze and using the Oculus Go head-mounted display (HMD) technology. The mechanics of the game require memorizing geometric shapes while the player progresses in two modes, autonomous or manual, with two levels of difficulty depending on the number of elements to remember. The application is developed in the Unity 3D video game engine considering the optimization of computational resources to improve the performance in the processing and maintaining adequate benefits for the user, while the generated data is stored and sent to a remote server. The maze task was assessed with 29 subjects in a controlled environment. The obtained results show a significant correlation between participants’ response accuracy in both the maze task and a face–pair test. Thus, the proposed task is able to perform memory assessments. © 2020 by the authors. Licensee MDPI, Basel, Switzerland.
Keywords: Biogeography of B. asper venom radiations; PCA of intraspecific venom variation; Snake venom; Venomics of Bothrops asper lineages